Reduced Electroencephalogram Complexity in Postoperative Delirium. Issue 3 (4th December 2021) - Tanabe, Sean; Parker, Maggie; Lennertz, Richard; Pearce, Robert A; Banks, Matthew I; Sanders, Robert D
Abstract: Delirium is associated with electroencephalogram (EEG) slowing and impairments in connectivity. We hypothesized that delirium would be accompanied by a reduction in the available cortical information (ie, there is less information processing occurring), as measured by a surrogate, Lempil-Ziv Complexity (LZC), a measure of time-domain complexity. Two ongoing perioperative cohort studies (NCT03124303, NCT02926417) contributed EEG data from 91 patients before and after surgery; 89 participants were used in the analyses. After cleaning and filtering (0.1–50Hz), the perioperative change in LZC and LZC normalized (LZCn) to a phase-shuffled distribution were calculated. The primary outcome was the correlation of within-patient paired changes in delirium severity (Delirium Rating Scale-98 [DRS]) and LZC. Scalp-wide threshold-free cluster enhancement was employed for multiple comparison correction. LZC negatively correlated with DRS in a scalp-wide manner (peak channel r 2 = .199, p < .001). This whole brain effect remained for LZCn, though the correlations were weaker (peak channel r 2 = .076, p = .010). Delirium diagnosis was similarly associated with decreases in LZC (peak channel p < .001). For LZCn, the topological significance was constrained to the midline posterior regions (peak channel p = .006). We found a negative correlation of LZC in the posterior and temporal regions with monocyte chemoattractant protein-1 (peak channel r 2 = .264, p < .001, n = 47) but not for LZCn. Complexity of the EEG signal fades proportionately to delirium severity implying reduced cortical information. Peripheral inflammation, as assessed by monocyte chemoattractant protein-1, does not entirely account for this effect, suggesting that additional pathogenic mechanisms are involved.